PERAN PREDICT OBSERVE EXPLAIN TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS V MATERI PERUBAHAN BENDA - Rahmawati, Ayu Wulan; Sujana, Atep; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2019)
Emphasize the science process skill, for maximizing students petential mixed up with discovery learning process. Then it takes skills that can facilitate this with science process skill. Learning which support science process skill was predict observe explain (POE) learning. This study aim to determine the role of POE Â learning to science process skills. The method of this research is quasi-experimental using non-equivalent control group design. Itâ€™s research population is all students of grade V elementary school in Sumedang Utara subdistriction. Sample technique is used purposive sampling and obtained sample that is SDN Sukaluyu as the experimental class and SDN Rancamulya as the control class. The instrumen is used a test instrument in the form of science process skill test, and non test instrument consists of teacher performance observation sheet and student activity, and student respon questionnaire. Based on the result of research, it is found that learning using POE learning has a positive effect in improving students science process skill in material changes ability significantly.